Diversity, density and distribution of termites in housing complexes in Purwokerto, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pratikno H, Haryanto T, Apriyanto DN. 2020. Diversity, density, and distribution of termites in housing complexes in Purwokerto City, Central Java Indonesia. Biodiversitas 21: 5729-5735. Termite attacks have detrimental effects on buildings and incur considerable costs. The rapid development of housing complex in Purwokerto City, Central Java Province, Indonesia urges an investigation on the occurrence of termite attacks. This research aimed to identify the diversity of termite species, its spatial distribution and its density on a variety of wood on housing complexes in Purwokerto City and the surrounding areas. The context of this study focused on wood species commonly used by the developers, namely albasia (Paraserianthes falcataria), which is commonly used for the upper ceiling, bangkirai (Shorea laevifolia) for poles and door/window frames, and teak (Tectona grandis) which is often used for door and window boards. We used bait techniques with the rationale that it is cheap and environmentally friendly as well as accurate. Four housing complexes in four subdistricts were randomly selected stratified based on four altitude ranges (
Keywords: altitude, housing, termites, wood durable quality.